A longitudinal characterization of perfusion in the aging brain and associations with cognition and neural structure. Issue 12 (7th May 2019) - Staffaroni, Adam M.; Cobigo, Yann; Elahi, Fanny M.; Casaletto, Kaitlin B.; Walters, Samantha M.; Wolf, Amy; Lindbergh, Cutter A.; Rosen, Howard J.; Kramer, Joel H.
Abstract: Cerebral perfusion declines across the lifespan and is altered in the early stages of several age‐related neuropathologies. Little is known, however, about the longitudinal evolution of perfusion in healthy older adults, particularly when perfusion is quantified using magnetic resonance imaging with arterial spin labeling (ASL). The objective was to characterize longitudinal perfusion in typically aging adults and elucidate associations with cognition and brain structure. Adults who were functionally intact at baseline ( n = 161, ages 47–89) underwent ASL imaging to quantify whole‐brain gray matter perfusion; a subset ( n = 136) had repeated imaging (average follow‐up: 2.3 years). Neuropsychological testing at each visit was summarized into executive function, memory, and processing speed composites. Global gray matter volume, white matter microstructure (mean diffusivity), and white matter hyperintensities were also quantified. We assessed baseline associations among perfusion, cognition, and brain structure using linear regression, and longitudinal relationships using linear mixed effects models. Greater baseline perfusion, particularly in the left dorsolateral prefrontal cortex and right thalamus, was associated with better executive functions. Greater whole‐brain perfusion loss was associated with worsening brain structure and declining processing speed. This study helps validate noninvasive MRI‐based perfusion imaging and underscores the importance of cerebral blood flow in cognitive aging.